Water and land in South Africa: economywide impacts of reform -- a case study for the Olifants river - Mukherjee, Natasha (International Food Policy Research Institute, 1996)
The paper presents a Watershed Computable General Equilibrium (CGE) Model for the Olifants River Catchment." A CGE provides an appropriate framework in which to explore policy alternatives for achieving more efficient water and land use.